WORKSHOP ORGANISASI DAN KEPEMIMPINAN BAGI PENGURUS IKATAN REMAJA MASJID DARUSSALAM - Kuswati, Yeti (JURNAL PARAHITA ABDIMAS: Jurnal Pengabdian Masyarakat, 2020)
Community service activities are motivated by problems faced by the Darussalam Mosque Youth Association regarding organization and leadership. To solve this problem, organizational and leadership workshops were held with the aim of strengthening the organizational structure and enhancing the role and function of the Mosque Youth Association in fostering the community, especially youth. The method used is a workshop for administrators and members of the Darussalam Mosque Youth Association. The material presented includes organizational identity, organizational structure, job descriptions, division of tasks, Statutes and Bylaws, the nature of leadership, leadership theory, leadership style, and Islamic leadership. Based on the evaluation, the results of the activity showed that both the process and the results were very good. In conclusion, organizational and leadership workshops can improve the knowledge, understanding, and skills of administrators and members of the Darussalam Mosque Youth Association in organizing organizations and strengthening leadership.